Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Midwives’ perspectives on (dis)respectful intrapartum care during facility-based delivery in sub-Saharan Africa: a qualitative systematic review and meta-synthesis - Bradley, Susan; McCourt, Christine; Rayment, Juliet; Parmar, Divya (Reproductive Health, 2019)
Background: In the past decade, the negative impact of disrespectful maternity care on women’s utilisation and experiences of facility-based delivery has been well documented. Less is known about midwives’ perspectives on these labour ward dynamics. Yet efforts to provide care that satisfies women’s psycho-socio-cultural needs rest on midwives’ capacity and willingness to provide it. We performed a systematic review of the emerging literature documenting midwives’ perspectives to explore the broader drivers of (dis)respectful care during facility-based delivery in the sub-Saharan African context. Methods: Seven databases (CINAHL, PsychINFO, PsychArticles, Embase, Global Health, Maternity and Infant Care and PubMed) were systematically searched from 1990 to May 2018. Primary qualitative studies with a substantial focus on the interpersonal aspects of care were eligible if they captured midwives’ voices and perspectives. Study quality was independently assessed by two reviewers and PRISMA guidelines were followed. The results and findings from each study were synthesised using an existing conceptual framework of the drivers of disrespectful care. Results: Eleven papers from six countries were included and six main themes were identified. ‘Power and control’ and ‘Maintaining midwives’ status’ reflected midwives’ focus on the micro-level interactions of the mother-midwife dyad. Meso-level drivers of disrespectful care were: the constraints of the ‘Work environment and resources’; concerns about ‘Midwives’ position in the health systems hierarchy’; and the impact of ‘Midwives’ conceptualisations of respectful maternity care’. An emerging theme outlined the ‘Impact on midwives’ of (dis)respectful care. Conclusion: We used a theoretically informed conceptual framework to move beyond the micro-level and interrogate the social, cultural and historical factors that underpin (dis)respectful care. Controlling women was a key theme, echoing women’s experiences, but midwives paid less attention to the social inequalities that distress women. The synthesis highlighted midwives’ low status in the health system hierarchy, while organisational cultures of blame and a lack of consideration for them as professionals effectively constitute disrespect and abuse of these health workers. Broader, interdisciplinary perspectives on the wider drivers of midwives’ disrespectful attitudes and behaviours are crucial if efforts to improve the maternity care environment - for women and midwives - are to succeed.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder